Open scholarship in Australia: A review of needs, barriers, and opportunities. (14th January 2021) - Arthur, Paul Longley; Hearn, Lydia; Montgomery, Lucy; Craig, Hugh; Arbuckle, Alyssa; Siemens, Ray
Abstract: Open scholarship encompasses open access, open data, open source software, open educational resources, and all other forms of openness in the scholarly and research environment, using digital or computational techniques, or both. It can change how knowledge is created, preserved, and shared, and can better connect academics with communities they serve. Yet, the movement toward open scholarship has encountered significant challenges. This article begins by examining the history of open scholarship in Australia. It then reviews the literature to examine key barriers hampering uptake of open scholarship, with emphasis on the humanities. This involves a review of global, institutional, systemic, and financial obstacles, followed by a synthesis of how these barriers are influenced at diverse stakeholder levels: policymakers and peak bodies, publishers, senior university administrators, researchers, librarians, and platform providers. The review illustrates how universities are increasingly hard-pressed to sustain access to publicly funded research as journal, monograph, and open scholarship costs continue to rise. Those in academia voice concerns about the lack of appropriate open scholarship infrastructure and recognition for the adoption of open practices. Limited access to credible research has led, in some cases, to public misunderstanding about legitimacy in online sources. This article, therefore, represents an urgent call for more empirical research around 'missed opportunities' to promote open scholarship. Only by better understanding barriers and needs across the university landscape can we address current challenges to open scholarship so research can be presented in usable and understandable ways, with data made more freely available for reuse by the broader public.